Catalyst for catalytic decomposition of hydrazine nitrate and hydroxylamine nitrate in nitric acid system and its application
By using a combination of metal carbide composite support and precious metal additives in the catalyst, the problem of loss and crushing of active components in the nitric acid system is solved, and efficient and stable decomposition of hydrazine nitrate and hydroxylamine nitrate is achieved, which extends the catalyst's Service life.
Patent Information
- Application Number
- CN202111476638.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-06
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-12-06
AI Technical Summary
The active components of existing catalysts are easily lost and easily broken in the nitric acid system, resulting in a short service life and the inability to effectively decompose hydrazine nitrate and hydroxylamine nitrate.
Using a metal carbide composite support catalyst composed of activated carbon, precious metals (such as Pt, Ru, Pd, Ir) and additives (such as Al, B), it can improve the strength and active components of the support through multiple impregnation preparation and calcination treatment. fixed, preventing loss and breakage.
Efficient catalytic decomposition of hydrazine nitrate and hydroxylamine nitrate under mild conditions significantly improves the stability and corrosion resistance of the catalyst, extends the service life, and avoids the collapse of the catalyst structure and particle breakage.
Smart Images

Figure CN116212910B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nuclear fuel post-processing, and in particular relates to a catalyst for catalytically decomposing hydrazine nitrate and hydroxylamine nitrate in a nitric acid system, and its preparation and application. Background Art
[0002] Nuclear fuel reprocessing technology is an important part of the nuclear industry. It refers to the treatment of nuclear fuel (spent fuel) used in nuclear reactors, the recovery of uranium and plutonium and other valuable elements therein, and the vitrification of highly radioactive wastes therein and sending them to deep geological disposal. At present, domestic and foreign reprocessing plants mainly use the Purex process, in which hydrazine and / or hydroxylamine are often used as stabilizers for low-oxidation actinide ions or as nitrite scavengers, and nitric acid waste liquid containing hydrazine nitrate and hydroxylamine nitrate is produced in the subsequent process. In the reprocessing process, sodium nitrite is usually added or nitrogen tetroxide gas is introduced to decompose hydrazine nitrate and hydroxylamine nitrate. Adding sodium nitrite will introduce salts into the system and increase the amount of waste liquid treated; although the introduction of N2O4 gas does not introduce salts, a large amount of radioactive aerosols will be generated, which will bring a great burden to the waste gas emission purification system. The decomposition of hydrazine nitrate and hydroxylamine nitrate by catalytic method has the advantages of not introducing other ions and small amount of waste liquid or waste gas treatment, and is a method worthy of study in the reprocessing process.
[0003] Since the late 1990s, domestic and foreign scholars have published many papers on the catalytic decomposition of hydrazine in the post-processing field. Ananiev et al. investigated the kinetics of Pt / SiO2 catalytic decomposition of hydrazine in nitric acid, non-nitric acid and weak base systems and speculated on its reaction mechanism [Radiochemistry, 2004, 46 (4): 377-384; Radiochemistry, 2004, 46 (6): 531-535; Appl. Cata A, General, 2003, 242: 1-10]. At the same time, they also studied the kinetics and reaction mechanism of Ru / SiO2 catalytic decomposition of hydrazine in nitric acid system [Radiochemistry, 2013, 55 (3): 279-286]. Ananiev et al. used oxide and oxide composite carriers to load Pt for catalytic decomposition of hydrazine and found that in nitric acid system, the sol effect of the oxide carrier reduced the activity of the catalyst [Radiochemistry, 2006, 48 (2): 119-124]. Chang Li et al. studied the effects of temperature, acidity and other conditions on the decomposition of hydrazine catalyzed by Pt-Ti in nitric acid [Nuclear Chemistry and Radiochemistry, 2005, 27(2):96-98]. At present, the research on the catalytic decomposition of hydrazine mainly focuses on the investigation of kinetics and process conditions, while there is less research on the optimization design of catalysts. At the same time, there are few reports on the decomposition of the mixed system of hydrazine and hydroxylamine.
[0004] Chinese patent CN112678939A discloses a method for removing a small amount of hydrazine nitrate and hydroxylamine nitrate from nitric acid. A catalyst with an "activated carbon-metal-silicon oxide" structure is used for the catalytic decomposition of a mixture of hydrazine nitrate and hydroxylamine nitrate. The catalyst has the advantages of high activity and long service life. However, during the experiment, the reaction temperature needs to be increased to extend the service life of the catalyst, indicating that the activity gradually decreases during the reaction. The researchers found that the active components of the catalyst were lost in the nitric acid system, and because this reaction is an in-situ large-scale gas production reaction, the catalyst was continuously eroded, and the catalyst was severely broken after 2830 hours of use.
[0005] Due to the problem that active components of current catalysts are easily lost and broken, it is necessary to further develop catalysts that are resistant to acid corrosion and have high strength and wear resistance. Summary of the invention
[0006] One of the technical problems to be solved by the present invention is to solve the problem of a catalyst for simultaneously catalyzing and decomposing hydrazine nitrate and hydroxylamine nitrate in a nitric acid system, and to provide a new catalyst which can efficiently catalyze and decompose hydrazine nitrate and hydroxylamine nitrate under mild conditions and has higher stability.
[0007] To solve one of the technical problems, the present invention adopts the following technical scheme: a catalyst for catalytically decomposing hydrazine nitrate and hydroxylamine nitrate in a nitric acid system comprises the following components by mass: 1) activated carbon, the remainder except other components; 2) an active component selected from one or more of Pt, Ru, Pd, and Ir, accounting for 1 to 10%; 3) an auxiliary agent selected from one or more of Al and B, accounting for 0.001 to 1%; 4) one or two selected from tungsten carbide and molybdenum carbide, accounting for 10 to 30% of the total mass of the activated carbon and the activated carbon.
[0008] The above-mentioned catalyst components: 1) the activated carbon is mesoporous activated carbon, and the remainder is; 2) the active component is preferably Ru, and the preferred content is 1-5%; 3) the auxiliary agent is preferably one or two of Al and B, and the preferred content is 0.01-0.5%; 4) one or two selected from tungsten carbide and molybdenum carbide, and the preferred content is 15-20% of the total mass of them and the activated carbon.
[0009] The second technical problem to be solved by the present invention is to adopt the method for preparing the catalyst described in the first technical problem above. The method uses metal carbide and activated carbon to form a composite carrier to improve the strength of the carrier, and then loads the active component and the auxiliary agent onto the composite carrier, which can effectively improve the interaction between the carrier and the active component to prevent the loss of the active component.
[0010] The catalyst preparation method comprises the following steps:
[0011] a) Preparation of MC-activated carbon composite carrier
[0012] 1) dispersing an activated carbon carrier in deionized water, adding a tungsten and / or molybdenum metal salt solution having a mass concentration of 10 to 20% dropwise under stirring, stirring at room temperature for 24 to 48 hours, evaporating the water, and drying at 120 to 200° C. for 12 to 24 hours to obtain an activated carbon precursor loaded with metal salts, wherein the tungsten and / or molybdenum loading is lower than the content in the target composite carrier;
[0013] 2) calcining the above precursor at 400-600° C. in H2, H2 / N2 or H2 / Ar atmosphere to obtain the MC-activated carbon composite carrier 1; the volume concentration of hydrogen in the atmosphere is 1-100%;
[0014] 3) dispersing the composite carrier 1 in deionized water instead of the activated carbon carrier, repeating the operations of steps 1) and 2) once or twice or more to obtain the target MC-activated carbon composite carrier 2 of the desired composition;
[0015] b) Preparation of supported metal catalysts
[0016] 1) Mix the noble metal salt solution and the auxiliary salt solution to form a solution, take the MC-activated carbon composite carrier 2, drop or pour the solution onto the MC-activated carbon composite carrier 2, the volume ratio of the solution to the activated carbon-composite carrier 2 is 0.1 to 10, and mix them evenly;
[0017] 2) soaking the mixture in step 1) at room temperature for 1 to 24 hours, and then drying at 100 to 200° C. for 1 to 24 hours;
[0018] 3) calcining the solid in step 2) at 200-400° C. for 2-6 hours under an inert gas atmosphere;
[0019] 4) reducing the solid in step 3) under hydrogen at 200-500° C. for 3-8 h.
[0020] Preparation steps of MC-activated carbon composite carrier 1) The specific surface area of activated carbon is 900-1200m 2 / g, pore diameter is 4-10nm, pore volume is 0.5-1.5cm 3 / g; in the MC-activated carbon composite carrier preparation step 1), the tungsten and / or molybdenum metal salt is ammonium tungstate and / or ammonium molybdate.
[0021] The noble metal ruthenium salt in the supported metal catalyst preparation step 1) is one or more of ruthenium trichloride and ruthenium acetate, the platinum salt is one or more of chloroplatinic acid and platinum tetrachloride, the Pd salt is one or more of palladium chloride and palladium nitrate, and the iridium salt is one or more of chloroiridic acid and iridium trichloride; the auxiliary Al and / or B compound in the supported metal catalyst preparation step 1) is aluminum nitrate or boric acid.
[0022] The present invention adopts multiple impregnations to prepare the MC-activated carbon composite carrier, which can effectively prevent the clogging of the carrier pores caused by a single impregnation, reduce the specific surface area of the carrier, and thus affect the distribution of the active component. At the same time, the high strength of the metal carbide is utilized to coat it on the surface of the activated carbon carrier, thereby improving the acid corrosion resistance of the carrier in the nitric acid system and the scouring of the carrier by in-situ gas production during the reaction. At the same time, the addition of the auxiliary agent Al or B can effectively fix the active component Ru on the carrier to prevent it from being lost.
[0023] The third technical problem to be solved by the present invention is to use the catalyst described in the first technical problem to realize the simultaneous catalytic decomposition process of hydrazine nitrate and hydroxylamine nitrate under nitric acid conditions. The technical solution is as follows: The catalyst can be used in a reactor or a fixed bed for the catalytic decomposition of hydrazine nitrate and hydroxylamine nitrate in a nitric acid system.
[0024] The hydrazine nitrate and hydroxylamine nitrate feed liquid is composed of an aqueous solution of 0.8-1.5 mol / L nitric acid, 0.05-0.2 mol / L hydrazine nitrate and 0.2-0.5 mol / L hydroxylamine nitrate. The feed liquid is stirred and mixed with a tributyl phosphate / n-dodecane solution with a volume concentration of 1%, and then allowed to stand and separate. The lower layer of feed liquid is used for catalytic decomposition reaction.
[0025] In the kettle reaction, the reaction temperature is 30-90°C, the catalyst mass to solution volume ratio is: 1:10-1:20g / mL; in the fixed bed reaction, the reaction temperature is 30-70°C, the liquid space velocity is 2-12h -1 .
[0026] The invention also discloses a method for preparing the catalyst. The catalysts hydrazine nitrate and hydroxylamine nitrate prepared by the invention have high decomposition activity, strong nitric acid corrosion resistance, and long service life, and the waste liquid treatment method is efficient, safe, economical, and environmentally friendly.
[0027] The beneficial effects of the present invention are:
[0028] (1) Compared with the prior art, the present invention effectively solves the problem of loss of active components of the catalyst in the nitric acid system and further improves the stability of the catalyst;
[0029] (2) The catalyst of the present invention is resistant to acid corrosion and abrasion in the nitric acid system and in-situ gas production reaction. The catalyst runs continuously for 3500 hours without breaking and the catalyst structure does not change, thus solving the problem of particle breakage and catalyst structure collapse during long-term operation of the catalyst in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 (a) is the test result of the residual concentration of hydroxylamine nitrate in the fixed bed stability experiment;
[0031] Figure 1(b) is the test result of the residual concentration of hydrazine nitrate in the fixed bed stability experiment;
[0032] Attached Figure 2 Loss trend of active component Ru in fixed bed stability experiment. DETAILED DESCRIPTION
[0033] The present invention is described in detail below through specific examples, but these examples do not limit the contents of the present invention.
[0034] Example 1
[0035] Take 8.12g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 12.9g of 10% ammonium tungstate solution was added dropwise under stirring. After the addition was completed, the mixture was stirred and immersed for 24h. Then, the mixture was evaporated to remove water, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a WC-AC composite carrier 1.
[0036] The prepared WC-AC composite carrier 1 was dispersed in 50 mL of deionized water, and 12.9 g of 10% ammonium tungstate solution was added under stirring. After the addition was completed, the mixture was stirred and impregnated for 24 h. The mixture was then evaporated to remove water, transferred to an oven, and dried at 120 ° C for 12 h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550 ° C to obtain a 20% WC-AC composite carrier 2, which was recorded as 20WC-AC.
[0037] Weigh 9.45g of 20WC-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and aluminum nitrate solution containing 0.625% aluminum mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%Al / 20WC-AC catalyst, recorded as catalyst 1.
[0038] Example 2
[0039] Take 8.12g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 12.9g of 10% ammonium tungstate solution was added dropwise under stirring. After the addition was completed, the mixture was stirred and immersed for 24h. Then, the mixture was evaporated to remove water, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a WC-AC composite carrier 1.
[0040] The prepared WC-AC composite carrier 1 was dispersed in 50 mL of deionized water, and 12.9 g of 10% ammonium tungstate solution was added under stirring. After the addition was completed, the mixture was stirred and impregnated for 24 h. The mixture was then evaporated to remove water, transferred to an oven, and dried at 120 ° C for 12 h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550 ° C to obtain a 20% WC-AC composite carrier 2, which was recorded as 20WC-AC.
[0041] Weigh 9.45g of 20WC-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and boric acid solution containing 0.625% boron mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%B / 20WC-AC catalyst, recorded as catalyst 2.
[0042] Example 3
[0043] Take 8.59g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 9.71g of 10% ammonium tungstate solution was added dropwise under stirring. After the addition was completed, the mixture was stirred and immersed for 24h. Then, the mixture was evaporated to remove water, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a WC-AC composite carrier 1.
[0044] The prepared WC-AC composite carrier 1 was dispersed in 50 mL of deionized water, and 12.9 g of 10% ammonium tungstate solution was added under stirring. After the addition was completed, the mixture was stirred and impregnated for 24 h. The mixture was then evaporated to remove water, transferred to an oven, and dried at 120 ° C for 12 h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550 ° C to obtain a 15% WC-AC composite carrier 2, which was recorded as 15WC-AC.
[0045] Weigh 9.45g of 15WC-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and aluminum nitrate solution containing 0.625% aluminum mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%Al / 15WC-AC catalyst, recorded as catalyst 3.
[0046] Example 4
[0047] Take 8.59 activated carbon (specific surface area of 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 9.71g of 10% ammonium tungstate solution was added dropwise under stirring. After the addition was completed, the mixture was stirred and immersed for 24h. Then, the mixture was evaporated to remove water, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a WC-AC composite carrier 1.
[0048] The prepared WC-AC composite carrier 1 was dispersed in 50 mL of deionized water, and 12.9 g of 10% ammonium tungstate solution was added under stirring. After the addition was completed, the mixture was stirred and impregnated for 24 h. The mixture was then evaporated to remove water, transferred to an oven, and dried at 120 ° C for 12 h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550 ° C to obtain a 15% WC-AC composite carrier 2, which was recorded as 15WC-AC.
[0049] Weigh 9.45g of 15WC-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and boric acid solution containing 0.625% boron mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%B / 15WC-AC catalyst, recorded as catalyst 4.
[0050] Example 5
[0051] Take 8.12g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 19.22g of 10% ammonium molybdate solution was added dropwise under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then, the water was evaporated to dryness, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a Mo2C-AC composite carrier 1.
[0052] The prepared Mo2C-AC composite carrier 1 was dispersed in 50mL of deionized water, and 19.22g of 10% ammonium molybdate solution was added under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then the water was evaporated and transferred to an oven and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a 20% Mo2C-AC composite carrier 2, which was recorded as 20Mo2C-AC.
[0053] Weigh 9.45g of 20Mo2C-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and aluminum nitrate solution containing 0.625% aluminum mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%Al / 20Mo2C-AC catalyst, recorded as catalyst 5.
[0054] Example 6
[0055] Take 8.12g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 19.22g of 10% ammonium molybdate solution was added dropwise under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then, the water was evaporated to dryness, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a Mo2C-AC composite carrier 1.
[0056] The prepared Mo2C-AC composite carrier 1 was dispersed in 50mL of deionized water, and 19.22g of 10% ammonium molybdate solution was added under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then the water was evaporated and transferred to an oven and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a 20% Mo2C-AC composite carrier 2, which was recorded as 20Mo2C-AC.
[0057] Weigh 9.45g of 20Mo2C-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and boric acid solution containing 0.625% boron mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%B / 20Mo2C-AC catalyst, recorded as catalyst 6.
[0058] Example 7
[0059] Take 8.59g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 14.42g of 10% ammonium molybdate solution was added dropwise under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then, the water was evaporated to dryness, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a Mo2C-AC composite carrier 1.
[0060] The prepared Mo2C-AC composite carrier 1 was dispersed in 50mL of deionized water, and 14.42g of 10% ammonium molybdate solution was added under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then the water was evaporated and transferred to an oven and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a 15% Mo2C-AC composite carrier 2, which was recorded as 15Mo2C-AC.
[0061] Weigh 9.45g of 15Mo2C-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and aluminum nitrate solution containing 0.625% aluminum mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%Al / 15Mo2C-AC catalyst, recorded as catalyst 7.
[0062] Example 8
[0063] Take 8.59g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 14.42g of 10% ammonium molybdate solution was added dropwise under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then, the water was evaporated to dryness, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a Mo2C-AC composite carrier 1.
[0064] The prepared Mo2C-AC composite carrier 1 was dispersed in 50mL of deionized water, and 14.42g of 10% ammonium molybdate solution was added under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then the water was evaporated and transferred to an oven and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a 15% Mo2C-AC composite carrier 2, which was recorded as 15Mo2C-AC.
[0065] Weigh 9.45g of 15Mo2C-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and boric acid solution containing 0.625% boron mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%B / 15Mo2C-AC catalyst, recorded as catalyst 8.
[0066] Comparative Example 1
[0067] Take 8.12g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL deionized water, and 25.8g of 10% ammonium tungstate solution was added dropwise under stirring. After the addition was completed, the mixture was stirred and impregnated for 24h. Then the mixture was evaporated to remove water, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a 20% WC-AC composite carrier, which was recorded as 20WC-AC.
[0068] Weigh 9.45g of 20WC-AC composite carrier into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and aluminum nitrate solution containing 0.625% aluminum mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%Al / 20WC-AC catalyst, recorded as catalyst 9.
[0069] Comparative Example 2
[0070] Take 8.12g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL deionized water, and 38.44g of 10% ammonium molybdate solution was added dropwise under stirring. After the addition was completed, stirring and impregnation were continued for 24h. Then, the water was evaporated and transferred to an oven and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a 20% Mo2C-AC composite carrier, which was recorded as 20Mo2C-AC.
[0071] Weigh 9.45g of 20Mo2C-AC composite carrier into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and aluminum nitrate solution containing 0.625% aluminum mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%Al / 20Mo2C-AC catalyst, recorded as catalyst 10.
[0072] Comparative Example 3
[0073] Take 9.45g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 100mL of deionized water, and 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration and aluminum nitrate solution containing 0.625% aluminum mass concentration were poured in, mixed evenly, and immersed for 24h. Dry at 120°C for 6h. The dried solid was transferred to a calcination tube and calcined at 400°C in an argon atmosphere for 4h. The calcined solid was then reduced at 300°C in a hydrogen atmosphere for 2h to obtain a 5%Ru-0.5%Al / AC catalyst, which was recorded as catalyst 11.
[0074] Comparative Example 4
[0075] Take 9.45g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 100mL of deionized water, and 8g of ruthenium trichloride solution containing 6.25% ruthenium was poured into it and mixed evenly, and then immersed for 24h. Drying was carried out at 120°C for 6h. The dried solid was transferred to a calcination tube and calcined at 400°C in an argon atmosphere for 4h. The calcined solid was then reduced at 300°C in a hydrogen atmosphere for 2h to obtain a 5%Ru / AC catalyst, which was recorded as catalyst 12.
[0076] Comparative Example 5
[0077] Take 8.12g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 12.9g of 10% ammonium tungstate solution was added dropwise under stirring. After the addition was completed, the mixture was stirred and immersed for 24h. Then, the mixture was evaporated to remove water, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a WC-AC composite carrier 1.
[0078] The prepared WC-AC composite carrier 1 was dispersed in 50 mL of deionized water, and 12.9 g of 10% ammonium tungstate solution was added under stirring. After the addition was completed, the mixture was stirred and impregnated for 24 h. The mixture was then evaporated to remove water, transferred to an oven, and dried at 120 ° C for 12 h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550 ° C to obtain a 20% WC-AC composite carrier 2, which was recorded as 20WC-AC.
[0079] Weigh 9.45g of 20WC-AC composite carrier 2 into a 100mL beaker, pour in 8g of ruthenium trichloride solution containing 6.25% ruthenium mass concentration, mix well, and soak for 24h. Dry at 120℃ for 6h. Transfer the dried solid to a calcination tube and calcine at 400℃ in an argon atmosphere for 4h. Reduce the calcined solid at 300℃ in a hydrogen atmosphere for 2h to obtain a 5%Ru / 20WC-AC catalyst, recorded as catalyst 13.
[0080] Comparative Example 6
[0081] Take 8.12g activated carbon (specific surface area 935m 2 / g, pore diameter is 4.5nm, pore volume is 0.65cm 3 / g) was dispersed in 50mL of deionized water, and 12.9g of 10% ammonium tungstate solution was added dropwise under stirring. After the addition was completed, the mixture was stirred and immersed for 24h. Then, the mixture was evaporated to remove water, transferred to an oven, and dried at 120°C for 12h. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a WC-AC composite carrier 1.
[0082] The prepared WC-AC composite carrier 1 was dispersed in 50 mL of deionized water, and 12.9 g of 10% ammonium tungstate solution was added under stirring. After the addition was completed, stirring and impregnation were continued for 24 hours. Then the water was evaporated and transferred to an oven and dried at 120°C for 12 hours. The dried solid was transferred to a calcination tube and carbonized and reduced in H2 at 550°C to obtain a 20% WC-AC composite carrier 2, which was recorded as catalyst 14.
[0083] Comparative Example 7
[0084] A 5% Ru / AC catalyst was prepared according to the catalyst preparation method described in Chinese patent CN112678939A and was recorded as catalyst 15.
[0085] Catalyst activity evaluation
[0086] The catalyst activity was preliminarily evaluated by using a kettle reaction. 100 ml of the feed liquid was composed of: 0.3 mol / L hydroxylamine nitrate, 0.1 mol / L hydrazine nitrate, 1.0 mol / L nitric acid solution (the feed liquid was stirred and mixed with a 1% tributyl phosphate / n-dodecane solution by volume before use, and the lower layer of the feed liquid was used for catalytic decomposition reaction) and poured into a 250 mL three-necked flask, and the three-necked flask was placed in a constant temperature magnetic stirring water bath pot, and the temperature was set to 60°C. After the temperature reached 60°C, 5.0 g of the catalyst dry product was added to the three-necked flask, the stirring speed was 400 rpm, and the reaction was timed. When there was no more bubble generation in the reaction system, the reaction was stopped, the reaction time was recorded, and the residual concentrations of hydroxylamine nitrate and hydrazine nitrate were sampled and analyzed. The experimental results are shown in Table 1.
[0087] Table 1 Experimental results of catalytic decomposition of hydroxylamine nitrate and hydrazine nitrate by different catalysts
[0088]
[0089]
[0090] The results show that the catalyst prepared by the present invention still maintains a relatively high reaction activity.
[0091] Catalyst stability evaluation
[0092] The stability and wear resistance of catalysts 1, 11, 12, 13, and 15 were evaluated using a fixed bed reaction mode. 7.5 g (dry weight) of the catalyst was loaded into a stainless steel reactor, and the outer wall of the reactor was tapped to make the catalyst layer densely packed. The reaction temperature was 60°C and the feed liquid to be treated was introduced into the reaction. The feed liquid flow rate was 0.5 mL / min. The feed liquid was composed of an aqueous solution of 1.0 mol / L nitric acid, 0.1 mol / L hydrazine nitrate, and 0.3 mol / L hydroxylamine nitrate. Before use, the feed liquid was stirred and mixed with a 1% volume concentration of tributyl phosphate / n-dodecane solution, and allowed to stand for stratification. The lower layer of feed liquid was used for catalytic decomposition reaction. During the operation of the device, samples were taken every day to detect the content of hydrazine nitrate and hydroxylamine nitrate in the effluent. The results are attached. Figure 1(a) , 1(b) The trend of ruthenium loss during the reaction is shown in the attached Figure 2 The structure of the catalyst after the reaction is shown in Table 2.
[0093] Table 2 Catalyst structure change data before and after stability test
[0094]
[0095]
[0096] The results show that the catalyst prepared with the composite carrier can remain stable in the nitric acid system, and its structure before and after the reaction has basically not changed. The catalyst with the addition of additives can effectively inhibit the loss of the active component Ru and improve the stability of the catalyst.
Claims
1. A catalyst for catalytically decomposing hydrazine nitrate and hydroxylamine nitrate in a nitric acid system, characterized in that: The catalyst comprises the following components by mass: 1) Activated carbon, the remainder after deducting other components; 2) The active component is Ru, accounting for 1-10%; 3) The additive is selected from one or more of Al and B, and the proportion is 0.001~1%; 4) One or both of tungsten carbide and molybdenum carbide, accounting for 10-30% of the total mass of tungsten carbide and activated carbon; The preparation method of the catalyst comprises the following steps: a) Preparation of MC-activated carbon composite carrier 1) Dispersing the activated carbon carrier in deionized water, adding a tungsten and / or molybdenum metal salt solution with a mass concentration of 10-20% dropwise under stirring, stirring at room temperature for 24-48 hours, evaporating the water, and drying at 120-200° C. for 12-24 hours to obtain an activated carbon precursor loaded with metal Ru salt, wherein the tungsten and / or molybdenum loading is lower than the content in the target composite carrier; 2) calcining the above precursor at 400-600°C in H2, H2 / N2 or H2 / Ar atmosphere to obtain the MC-activated carbon composite carrier 1; the volume concentration of hydrogen in the atmosphere is 1-100%; 3) The composite carrier 1 is dispersed in deionized water instead of the activated carbon carrier, and the operations of steps 1) and 2) are repeated once or twice or more to obtain the target MC-activated carbon composite carrier 2 of the desired composition; b) Preparation of supported metal catalysts 1) Mix the noble metal salt solution and the auxiliary salt solution to form a solution, take the MC-activated carbon composite carrier 2, drop or pour the solution onto the MC-activated carbon composite carrier 2, the volume ratio of the solution to the activated carbon-composite carrier 2 is 0.1-10, and mix them evenly; 2) soaking the mixture in step 1) at room temperature for 1 to 24 hours, and then drying at 100 to 200° C. for 1 to 24 hours; 3) calcining the solid in step 2) at 200-400° C. for 2-6 hours under an inert gas atmosphere; 4) The solid in step 3) is reduced under hydrogen at 200-500°C for 3-8h.
2. The catalyst according to claim 1, characterized in that: The catalyst component: The additive content is 0.01~0.5%; One or both of tungsten carbide and molybdenum carbide, the content of which is 15-20% of the total mass of tungsten carbide and activated carbon.
3. The catalyst according to claim 1, characterized in that: Preparation steps of MC-activated carbon composite carrier 1) The specific surface area of activated carbon is 900~1200 m 2 / g, pore diameter is 4~10nm, pore volume is 0.5~1.5cm 3 / g; in the MC-activated carbon composite carrier preparation step 1), the tungsten and / or molybdenum metal salt is ammonium tungstate or ammonium molybdate.
4. The catalyst according to claim 1, characterized in that: The noble metal ruthenium salt in the supported metal catalyst preparation step 1) is one or both of ruthenium trichloride and ruthenium acetate; the auxiliary agent Al and / or B compound in the supported metal catalyst preparation step 1) is aluminum nitrate and / or boric acid.
5. The use of the catalyst according to any one of claims 1 to 4, characterized in that: The catalyst is used in a reaction kettle or a fixed bed for catalytic decomposition of hydrazine nitrate and hydroxylamine nitrate in a nitric acid system.
6. The use of the catalyst according to claim 5, characterized in that: The hydrazine nitrate and hydroxylamine nitrate feed solutions are composed of an aqueous solution of 0.8-1.5 mol / L nitric acid, 0.05-0.2 mol / L hydrazine nitrate and 0.2-0.5 mol / L hydroxylamine nitrate.
7. Use of the catalyst according to claim 5 or 6, characterized in that: In the autoclave reaction, the reaction temperature is 30-90°C, and the catalyst mass to solution volume ratio is 1:10-1:20 g / mL; In fixed bed reaction, the reaction temperature is 30-60℃ and the liquid space velocity is 2-12h -1 .